2009
DOI: 10.1021/es900250d
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Sustainability Factors Associated With Next-Generation Biofuels in the U.S.: What Do We Really Know?

Abstract: In this paper, we assess what is known or anticipated about environmental and sustainability factors associated with next-generation biofuels relative to the primary conventional biofuels (i.e., corn grain-based ethanol and soybean-based diesel) in the United States during feedstock production and conversion processes. Factors considered include greenhouse (GHG) emissions, air pollutant emissions, soil health and quality, water use and water quality, wastewater and solid waste streams, and biodiversity and lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
107
1
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(116 citation statements)
references
References 85 publications
2
107
1
4
Order By: Relevance
“…This knowledge will be used to produce the next generation of biofuel crops by increasing fatty acid content and by optimizing the hydrolysis of plant cell walls to release fermentable sugars. Introduction Biofuels are commonly defined as fuels derived from renewable biological products and are often regarded as an attractive, 'green' alternative to fossil sources of energy due to their potential contribution to lowering carbon dioxide emissions [1]. Globally, plants produce an estimated 200 billion tones of biomass per year [2] in the form of sugars, polysaccharides, oils and other biopolymers, representing an unprecedented resource for biofuel production.…”
mentioning
confidence: 99%
“…This knowledge will be used to produce the next generation of biofuel crops by increasing fatty acid content and by optimizing the hydrolysis of plant cell walls to release fermentable sugars. Introduction Biofuels are commonly defined as fuels derived from renewable biological products and are often regarded as an attractive, 'green' alternative to fossil sources of energy due to their potential contribution to lowering carbon dioxide emissions [1]. Globally, plants produce an estimated 200 billion tones of biomass per year [2] in the form of sugars, polysaccharides, oils and other biopolymers, representing an unprecedented resource for biofuel production.…”
mentioning
confidence: 99%
“…Growing grain crops probably has the greatest detrimental impact on biodiversity if these crops are managed more intensively, with increased inputs and fewer rotations (Dyer et al, 2011). Growing perennial herbaceous crops on marginal land can often reduce biodiversity loss compared to using the land for row crops such as corn (Williams et al, 2009). However, Dyer et al (2011) found that if the marginal land is natural grassland, such as much of the rangeland in Western Canada, rather than the result of land degradation, even a perennial feedstock crop (such as switchgrass) could result in the loss of extensive areas of natural habitat.…”
Section: Greenhouse Gas Emissionsmentioning
confidence: 99%
“…The balance between the residue removal rate and long-term soil health is a challenge (Williams et al, 2009). Soil erosion is affected by crop type and its production practices.…”
Section: Sustaining Land Productivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Although several researchers have compiled LCA studies of lignocellulosic ethanol to discuss some of the key issues: energy pathways, system boundaries, functional units, allocation methods, utilization of coproducts etc. 14,23,24,42,63,77,81,88,111,132 , some recent advances in LCAs of lignocellulosic bioethanol remain to be reported. Therefore, this study aims to compile recent LCA studies of lignocellulosic bioethanol, and discuss the energetic, environment and socioeconomic aspects of the bioethanol industry.…”
Section: Introductionmentioning
confidence: 99%